IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH NEWS RETELLING - Irhamah Irhamah; Asdar Asdar; A. Hamsiah A. Hamsiah (Publikasi dan UKI Press UKI Toraja., 2022)
This paper involves researching, Improving The Students’ Speaking Through News Retelling. A Thesis. Language and Arts Faculty of State University of Makassar. The objective of the research was to find out whether the use of English News Retelling can improve students’ speaking ability. The research applied a pre- experimental meyhod with one group pretest and posttest design. The pre-test was given to know to what extent the students speaking ability and post-test was given to identify the students achievement after treatment. The population of this research was the second year students os SMK Tamalatea Makassar and used purposive sampling technique. The variable of the research were the use of English News Retelling as the independent variable and the students speaking ability as dependent variable. The result of the data indicate that was significant difference between the mean score of pre-tset and the post-test of the students. The value of t-table (1.729) was higer than t-test (34.0) at level of significant (p)= 0.5 and the degree of freedom (df)= n-1 . it can be concluded that English New retelling can improve students speaking ability